The nudibranch names mentioned as n.sp. in Bergh (1861) are almost all nomina nuda (Gastropoda: Heterobranchia: Nudibranchia) - Jensen, Kathe; Nielsen, Claus (Zootaxa, 2013)
In a publication in Danish from 1861, Bergh described the nematocysts found in a number of nudibranch species. Many of the species had been described previously, but a number were new and given names, but without a description. These species are nomina nuda. We have translated the “descriptions”, including the foot-notes, and reproduced the original plate to show that only the nematocysts (real or assumed) were described. The only species given a short description fulfilling the requirements of the ICZN is Pleurophyllidia quadrilateralis, which was described as the only species in the new genus Sancara. This in turn was shown to be a junior synonym of Linguella de Blainville, 1823. All the species were subsequently described anatomically in detail and made valid in a number of papers, and most of the type material is located in the Zoological Museum, Copenhagen (Natural History Museum of Denmark). The names in current use have been given.